The Effect of Adding Avocados (Persea americana) on Microbiological and Chemical Qualities in Yoghurt Drinks - Fatimah, Siti Alihatus; Agustini, Rudiana (Jurnal Pijar Mipa, 2024)
Yoghurt is one of the fermented products from cow's milk and skim milk as a source of protein to cover nutritional needs. With the development of innovation and the creation of food products, yogurt has many flavors from various fruits and vegetables. Yogurt food product innovations can also be made from skim milk combined with the addition of avocados. Avocado is a fruit that contains fiber, riboflavin (B2), niacin (B3), vitamins A, C, E, K, vitamin B6, magnesium, glutathione, and unsaturated fatty acids. The purpose of this study was to describe the effect of the concentration of avocados (Persea americana) on the quality of microbiology (total LAB) and chemistry (pH, fat content, and protein content) in yogurt drinks. The research used laboratory experimental methods, and data analysis was done descriptively. The treatment of adding avocados is 0%, 10%, 15%, and 20%. The results of the study obtained the effect of the concentration value of adding avocados (Persea americana) with the results of the study: the total value of LAB increased from 4.1x109±0.20 CFU/mL (10%) to 4.4x109±0.07 CFU/mL (15%), the pH value decreased from 4.30±0.02 (0%) to 3.89±0.01 (20%), The fat content value increased from 0.05±0.007 % w/b (0%) to 0.57±0.005 % w/b (20%), the protein content value decreased from 3.46±0.02% w/b (0%) to 2.94b±0.00 % w/b (20%). The conclusion of this study is the effect of adding avocados (Persea americana) on the quality of microbiology (total LAB) and chemistry (pH, fat content, and protein content) in yogurt drinks.